(untitled) - Rodman, George (New York, 2011)
Mass Media in a Changing World helps students understand media in today's world through a unique structure that makes the material easily intelligible and meaningful to their lives. Each chapter is divided into three-part narrative sections: history, industry, and controversy. This text tells the story of where the media came from, why they do what they do, and why those actions cause controversies. Students will develop an ability to analyze the ways in which we use mass media to change the world. The updated third edition includes current examples (often found in the new close-ups and new chapter openers), updated statistics, and rewritten sections that provide a treatment of new concepts and events that have evolved over the last year.
Keywords: Mass media,Thông tin đai chúng